The Construction of Legal Protection for Journalists Unaffiliated with Press Companies in the Industrial Revolution 4.0 Era - Santoso, Budi; Azhari, Aidul Fitriciada; ., Absori (International Journal of Membrane Science and Technology, 2023)
This paper aims to: (1) analyze the legal protection for journalists unaffiliated with press companies and (2) formulate a construction of legal protection for journalists unaffiliated with press companies in the Industrial Revolution 4.0 era in Indonesia. This normative legal research applied the statute and conceptual approaches. Results showed that: (1) Journalists unaffiliated with press companies only obtain protection from the state based on Article 8 Law of the Press although they do not feel the benefit of such a protection and (2) The construction of legal protection for journalists that are unaffiliated with press companies has an emphasis on the revision of Article 8 Law of the Press which should explain the type of legal protection obtained, considering that more journalists use online media to publish their work. Multi-interpretable articles of the Amended Law on Electronic Information and Transaction should also be revised to prevent the criminalization of journalists.